Penerapan Pendidikan Karakter Berbasis Nilai Pancasila Sila Ke-4 di MA Al Fattahiyyah Ngranti-Boyolangu-Tulungagung - Sofiyudin, Muhamad; Djatmiko, Andreas Andrie (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to identify the forms and impacts of implementing character education based on the fourth principle of Pancasila in class XI students at MA Al Fattahiyyah Tulungagung. A qualitative descriptive approach was used with data collection techniques including observation, interviews, and documentation. The findings indicate that the application of democratic values is manifested through deliberations, democratic class leader elections, and group discussions that encourage open opinion sharing. Implementation challenges include low student participation due to lack of self-confidence and learning motivation. Nevertheless, character education based on the fourth Pancasila principle positively influences the development of democratic attitudes and togetherness among students. The success of this implementation largely depends on the role of teachers, school environment, and family support.